Organ‐Specific Responses to Nivolumab Plus Ipilimumab in Advanced Hepatocellular Carcinoma: A Multicenter, Retrospective Study - Jung Sun Kim; Youngun Kim; Beodeul Kang; Ilhwan Kim; Hyeyeong Kim; Won Suk Lee; Jung Yong Hong; Ho Yeong Lim; Han Sang Kim; Chang Gon Kim; Sanghoon Jung; Chansik An; et al. (Cancer Medicine)
ABSTRACT Background Immune checkpoint inhibitor (ICI) monotherapy elicits limited intrahepatic responses in patients with advanced hepatocellular carcinoma (HCC). Here, we investigate the organ‐specific objective response rate (OSORR) of nivolumab plus ipilimumab (Nivo/Ipi) combination treatment, considering prior ICI exposure, compared with nivolumab (Nivo) monotherapy. Methods We analyzed 204 lesions from Nivo/Ipi‐treated and 305 lesions from Nivo‐treated patients with advanced HCC at five referral cancer centers in Korea. Organ‐specific response criteria were adopted from Response Evaluation Criteria in Solid Tumors 1.1, according to the indicated sites: the liver, lung, lymph nodes (LNs), and other metastatic sites. Results Nivo/Ipi combination therapy showed OSORRs of 18.1% in the liver, 17.7% in the lungs, 30.0% in LNs, and 12.5% in other metastatic sites. Patients without prior ICI exposure had OSORRs of 29.0% in the liver, 31.3% in the lungs, 33.3% in LNs, and 23.1% in other metastatic sites (72 individual lesions). Conversely, patients with prior ICI exposure had OSORRs of 11.5% in the liver, 11.4% in the lung, 27.8% in LNs, and 7.4% in other metastatic sites (132 individual lesions). Furthermore, patients who achieved a response in the liver or the lung had longer progression‐free and overall survival, compared with those without responses. Nivo monotherapy yielded OSORRs of 13.5%, 25.3%, 39.3%, and 18.4% in the liver, lungs, LNs, and other metastatic sites, respectively. Conclusion Nivo/Ipi combination therapy induced superior intrahepatic responses compared to Nivo monotherapy in patients with advanced HCC without prior ICI exposure, highlighting its potential to overcome liver‐specific immune tolerance.